Determination Of Budi Darma University Ordering Patterns Needs With Apriory Algorithm - Hery Sunandar; Abdul Sani Sembiring (Sean Institute, 2021)
In a university, office stationery is needed to support the teaching and learning process, one of which is paper, markers, ink and so on. In determining the right strategy in terms of purchasing stationery, an effective analysis is needed, to reduce excessive spending. One way that can be done to order stationery is to use data mining techniques. The data mining technique used in this case is to use the Apriori algorithm. The a priori algorithm is one of the classical data mining algorithms. The a priori algorithm is used so that computers can learn association rules, look for patterns of relationships between one or more items in a dataset. This research was conducted by observing several research variables that are often considered by universities in ordering office stationery. (ATK). The results of this study are in the form of interesting patterns of data mining results which are important information to support ordering stationery